1996 ILRI project workplans - International Livestock Research Institute (International Livestock Research Institute, 1996)
This Report is divided into six parts according to ILRI's programmes, viz, Conservation of Biodiversity, Production Systems Research, Utilization of Tropical Feed Resources, Animal Health Improvement, Livestock Policy analysis, and Strengthening Collaboration with National Agricultural Research Systems. Each programme is again divided into projects. This paper outlines the workplans of each project with, particularly reference to location, scientists involved, collaborators, background and justification, objectives, workplan for 1996, expected output, project publication and budget.